The Effectiveness, Safety and Outcome of Low Dose Aspirin for The Prevention of Superimposed Preeclampsia in Women with Chronic Hypertension : A Comprehensive Systematic Review - Andi Muh. Ariansyah Nazaruddin; Pramuliansyah Haq (International Medical Journal Corp. Ltd, 2024)
Background: Low-dose aspirin therapy has been shown to reduce pregnancy-related complications, including pre-eclampsia, in pregnant women with chronic hypertension. However, mixed findings suggest that it does not significantly alter the likelihood of developing superimposed pre-eclampsia, preterm birth, or perinatal mortality in women with chronic hypertension. Methods: This systematic review complied with the PRISMA 2020 requirements, concentrating solely on full-text papers published in English from 2014 to 2024. Editorials and review articles lacking a DOI were omitted to guarantee the use of high-quality sources. A comprehensive literature review was performed using esteemed databases such as ScienceDirect, PubMed, and SagePub to locate pertinent studies. Result: The initial database search identified over 200 publications relevant to the topic. Following a meticulous three-stage screening process, eight studies were selected that met the predefined inclusion criteria for comprehensive analysis. These studies were subjected to a rigorous critical evaluation, providing an in-depth investigation into the effectiveness, safety, and outcomes of low-dose aspirin for the prevention of superimposed pre-eclampsia. This focused approach ensured that the analysis drew from high-quality evidence directly aligned with the study's objectives. Conclusion: Superimposed preeclampsia, a condition causing preterm birth and neonatal intensive care unit admissions, is a risk for chronic hypertension women. Aspirin, a low-dose medication, has shown mixed efficacy in preventing this condition, with dose-dependent effectiveness.